Toward personalized management of chronic hypertension in pregnancy - Magee, Laura A. (Am J Obstet Gynecol, 2022)
Chronic hypertension complicates 1% to 2% of pregnancies, and it is increasingly common. Women with chronic hypertension are an easily recognized group who are in touch with a wide variety of healthcare providers before, during, and after pregnancy, mandating that chronic hypertension in pregnancy be within the scope of many practitioners. We reviewed recent data on management to inform current care and future research. This study is a narrative review of published literature. Compared with normotensive women, women with chronic hypertension are at an increased risk of maternal and perinatal complications. Women with chronic hypertension who wish to be involved in their care can do by measuring blood pressure at home. Accurate devices for home blood pressure monitoring are now readily available. The diagnostic criteria for superimposed preeclampsia remain problematic because most guidelines continue to include deteriorating blood pressure control in the definition. It has not been established how angiogenic markers may aid in confirmation of the diagnosis of superimposed preeclampsia when suspected, over and above information provided by routinely available clinical data and laboratory results. Although chronic hypertension is a strong risk factor for preeclampsia, and aspirin decreases preeclampsia risk, the effectiveness specifically among women with chronic hypertension has been questioned. It is unclear whether calcium has an independent effect in preeclampsia prevention in such women. Treating hypertension with antihypertensive therapy halves the risk of progression to severe hypertension, thrombocytopenia, and elevated liver enzymes, but a reduction in preeclampsia or serious maternal complications has not been observed; however, the lack of evidence for the latter is possibly owing to few events. In addition, treating chronic hypertension neither reduces nor increases fetal or newborn death or morbidity, regardless of the gestational age at which the antihypertensive treatment is started. Antihypertensive agents are not teratogenic, but there may be an increase in malformations associated with chronic hypertension itself. At present, blood pressure treatment targets used in clinics are the same as those used at home, although blood pressure values tend to be inconsistently lower at home among women with hypertension. Although starting all women on the same antihypertensive medication is usually effective in reducing blood pressure, it remains unclear whether there is an optimal agent for such an approach or how best to use combinations of antihypertensive medications. An alternative approach is to individualize care, using maternal characteristics and blood pressure features beyond blood pressure level (eg, variability) that are of prognostic value. Outcomes may be improved by timed birth between 38 0/7 and 39 6/7 weeks’ gestation based on observational literature; of note, confirmatory trial evidence is pending. Postnatal care is facilitated by the acceptability of most antihypertensives (including angiotensin-converting enzymes inhibitors) for use in breastfeeding. The evidence base to guide the care of pregnant women with chronic hypertension is growing and aligning with international guidelines. Addressing outstanding research questions would inform personalized care of chronic hypertension in pregnancy.